Firm-Specific Determinants of Profitability of Listed Commercial Services Companies in Kenya and Tanzania - Lyimo, Gregory D.; Walter, Gloria (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The issue on whether firm-specific determinants such as capital adequacy, financial leverage, company liquidity and firm size influence the profitability of listed commercial services companies is still debatable to date. Therefore, this study examines the firm-specific determinants of profitability of listed commercial services companies at Dar es Salaam Stock Exchange (DSE) and Nairobi Stock Exchange (NSE) in Tanzania and Kenya respectively. The study used data extracted from annual reports of eleven commercial services companies from 2015 to 2020 yielding 66 firm-year observations. Moreover, panel data regression analysis specifically a random effect estimator was employed to estimate firm-specific determinants of profitability of commercial services companies listed in Tanzania and Kenya. The study found out that capital adequacy was significantly positively linked to the profitability of listed commercial services companies at DSE and NSE. Likewise, the study revealed that firm size was significantly positively associated with the profitability of commercial services listed at DSE and NSE. Moreover, the study uncovered an insignificant positive association between profitability and both financial leverage and liquidity of commercial services companies listed at DSE and NSE. The results suggested that corporate managers are advised to increase investment in equity through selling equities to the general public and private shareholders so as to increase profitability. Furthermore, corporate managers are advised to increase firm size to enhance profitability.